Women and islam in Bangladesh : beyond subjection and tyranny - Hashmi, Taj I. (Hampshire : MacMillan Press, 2000)
Social sciences
Keywords: Women; Muslim women; Social conditions; Women in islam; Empowerment; Feminism; Patriarchy